Customer Satisfaction is Reviewed From Product Design and After Sales Service With Mediation of Purchasing Decisions - Muchammad Sholeh; Ida Aryati DPW; Sudarwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The study aims to determine the Influence of Product Design, Product Quality, After-Sales Service and Brand Image on Purchasing Decisions on CV. Shofa Erterprises Sejahtera Bekasi by collecting data using questionnaires. The location used for research is CV. Shofa Erterprises Sejahtera Bekasi and The research time starts from July – December 2023. The population in this study were CV clients. Shofa Erterprises Sejahtera Bekasi in the last 5 years with a total of 120 people. The sampling technique in this study uses a non-proportability sampling approach with Saturation Sampling Sampling Technique, which is a sampling technique using a total of 120 consumers for the last 5 years. The data collection methods used in this study were observation, documentation, questionnaires, and literature studies. The data analysis technique used in this study uses SEM and is based on Partial Least Square / PLS. Based on the research that has been done, the following conclusions can be drawn Product design has a significant effect on consumer satisfaction, Product design has a significant effect on purchasing decisions, Purchasing decisions have a significant effect on consumer satisfaction, After-sales service has a significant effect on consumer satisfaction, After-sales service has a significant effect on purchasing decisions, Product design has a significant effect on consumer satisfaction with Mediated purchasing decisions, after-sales service has a significant effect on consumer satisfaction with mediated purchasing decisions.